Některé aspekty využití solární energie pro obytné budovy - Straka, Roman; Siegl, Milan (Univerzita Pardubice, 2003)
In this paper a problem of solar energy application for housing heating is analysed. First part of the publication describer certain projects with solar energy used in so called experimental ecological houses with low energy consumption. Second part shows solar system implementation into three panel houses in the City of Pardubice particularly for hot water supply. Total cost of the solar system and energy unit price were computed and comparedwith price from classical energy source used. Sola energy cost came approximately three times higher in comparison with the current energy system.
Keywords: sluneční energie; obytné budovy; aplikace